Incorporating ifosfamide into salvia oil-based nanoemulsion diminishes its nephrotoxicity in mice inoculated with tumor - AlMotwaa, Sahar M. (Bioimpacts, 2020)
[Image: see text] Introduction: Nephrotoxicity is one of the major side effects of the chemotherapeutic drug, ifosfamide (IFO). In this study, IFO was solubilized in nanoemulsion (NE) containing salvia (SAL) essential oil to investigate its adverse side effects in mice. Methods: One hundred female Swiss albino mice (n = 20/group) were split into five groups. Group I (Normal) received saline solution (0.9% (w/v) NaCl) while groups II-V were intraperitoneally (I.P.) injected with 2.5 × 10(6) Ehrlich ascetic carcinoma (EAC) cells/mouse. Group II (EAC) represented the untreated EAC-bearing mice. Group III (IFO) was treated with IFO at a dose of 60 mg/kg/d (I.P. 0.3 mL/mouse). Group IV (SAL) was treated with 0.3 mL blank NE-based SAL oil/mouse. Group V (SAL-IFO) was treated with IFO, loaded in 0.3 mL of blank SAL-NE, at a dose of 60 mg/kg/d (I.P. 0.3 mL/mouse). Groups III-V were treated for three consecutive days. Results: There was a double increase in the survival percentage of the SAL-IFO group (60%) relative to the IFO group (30%). Renal damage with the presence of Fanconi syndrome was indicated in the IFO group through a significant elevation in the levels of serum creatinine, blood urea nitrogen, urine bicarbonate, and phosphate in addition to a reduced level of glucose compared to the normal group. On the other hand, the administration of SAL-IFO into the mice reversed this effect. Additionally, the oxidative stress in the kidney tissues of the SAL-IFO group was ameliorated when compared to the IFO group. Conclusion: Incorporating IFO into SAL-NE has protected the kidneys from the damage induced by IFO.